MicroRNA-124 Overexpression in Schwann Cells Promotes Schwann Cell-Astrocyte Integration and Inhibits Glial Scar Formation Ability - Li, Zhijun; Yu, Yifei; Kang, Juanjuan; Zheng, Yangyang; Xu, Jinying; Xu, Kan; Hou, Kun; Hou, Yi; Chi, Guangfan (Frontiers in Cellular Neuroscience, 2020)
Schwann cell (SC) transplantation is a promising approach for the treatment of spinal cord injury (SCI); however, SC grafts show a low migratory capacity within the astrocytic environment, which inevitably hampers their therapeutic efficacy. The purpose of this study was to explore mechanisms to modify the characteristics of SCs and astrocytes (ASs), as well as to adjust the SC-AS interface to break the SC-AS boundary, thus improving the benefits of SCI treatment. We observed that the expression levels of miR-124 in SCs and astrocytes were significantly lower than those in the normal spinal cord. Furthermore, overexpressing miR-124 in SCs (miR-124-SCs) significantly inhibited gene and protein expression levels of SC-specific markers, such as GFAP and Krox20. The expression of neurotrophic factors, Bdnf and Nt-3, was up-regulated in miR-124-SCs without affecting their proliferation. Further, the boundary assay showed an increased number of miR-124-SCs that had actively migrated and entered the astrocytic region to intermingle with astrocytes, compared with normal SCs. In addition, although Krox20 protein expression was down-regulated in miR-124-SCs, the luciferase assay showed that Krox20 is not a direct target of miR-124. RNA sequencing of miR-124-SCs revealed seven upregulated and eleven downregulated genes involved in cell migration and motility. Based on KEGG pathway and KOG functional analyses, changes in these genes corresponded to the activation of Hippo, FoxO, and TGF-beta signaling pathways, cytokine-cytokine receptor interactions, and the cell cycle. Finally, co-culturing of miR-124-SCs and astrocytes in a transwell system revealed that GFAP and p-STAT3 protein expression in astrocytes was significantly reduced. Collectively, these results show that overexpression of miR-124 in SCs promotes SC-AS integration in vitro and may attenuate the capacity of astrocytes to form glial scars. Thus, this study provides novel insights into modifying SCs by overexpressing miR-124 to improve their therapeutic potential in SCI.